A Prospective Cohort Study of Menstrual Characteristics and Time to Pregnancy - Wise, Lauren A. (Oxford University Press, 2011)
The authors examined the association between menstrual characteristics and time to pregnancy among 2,653 Danish women enrolled in a prospective cohort study (2007–2009). Menstrual characteristics were reported at baseline. Outcome data were updated bimonthly until pregnancy, fertility treatment, loss to follow-up, or end of observation (12 cycles). Adjusted fecundability ratios and 95% confidence intervals were estimated by using discrete-time Cox regression models. Relative to average cycle lengths (27–29 days), fecundability ratios for cycle lengths <25, 25–26, 30–31, 32–33, and ≥34 days were 0.64 (95% confidence interval (CI): 0.49, 0.84), 0.94 (95% CI: 0.77, 1.13), 1.10 (95% CI: 0.97, 1.25), 1.35 (95% CI: 1.06, 1.73), and 1.17 (95% CI: 0.91, 1.49), respectively. Compared with cycles that regularized within 2 years after menarche, fecundability ratios for cycles that regularized 2–3 and ≥4 years after menarche were 0.90 (95% CI: 0.80, 1.02) and 0.89 (95% CI: 0.77, 1.03), respectively. Fecundability ratios were 0.87 (95% CI: 0.72, 1.05) comparing <3 with 3–4 days of menstrual bleeding and 0.70 (95% CI: 0.43, 1.13) comparing very heavy with moderate flow. In the present study, shorter cycle length was associated with delayed time to pregnancy. Age at menarche, time to menstrual regularization, and duration or intensity of menstrual flow were not appreciably associated with fecundability.